Specificity of the hierarchical system of the Eastern Catholic Churches - NOWICKA, URSZULA (Prawo Kanoniczne, 2013)
A matter of the hierarchical system is one of the specific issues regulated in CCEO. Its specificity is expressed in the fact that four hierarchical types of Eastern Churches sui iuris are known in the eastern legislature. The hierarchical type of Eastern Church depends on its importance given to it by the supreme ecclesiastic authority. Resulting in a major or minor rank of its autonomy. These are namely: the patriarchal Churches, Archbishop’s Churches, Larger Metropolitan Churches and other sui iuris Churches. The subject of the article is analysis further Codex standards, as well as taking into the account the internal administrative division of Churches and the characteristic to the eastern law the designation way of eastern bishops.